Bedrock geology of the Nunatarssuaq area, Northwest Greenland - Fernald, A. T.; Horowitz, A. S. (Meddelelser om Grønland, 1964)
All the rocks of the Nunatarssuaq area of northwest Greenland are of Precambrian age. The basement complex, of early or middle Precambrian age, is composed of amphibolite, porphyroblastic gneiss, banded gneiss, and migmatite, cut by numerous pegmatite dikes and a single granitic stock. This complex is unconformably overlain by gently dipping conglomerate and sandstone of the Thule group, of late Precambrian age. Diabase dikes, probably also of late Precambrian age, cut both the basement complex and the Thule group. The principal structural elements of the basement complex are northwest strikes and variable dips of the foliation, possibly two northwest trending anticlines and a northwest plunging syncline, and two sets of steeply dipping joints that trend northwest and northeast, along which the diabase dikes have been injected. All rocks were affected by block faulting and tilting, probably in Cretaceous or Tertiary time.